Beberapa Faktor yang Berpengaruh terhadap Barotrauma Membran Timpani pada Penyelam Tradisional di Wilayah Kabupaten Banyuwangi - Sugianto Sugianto; Suharyo Hadisaputro; Supriharti Supriharti; Munasik Munasik; Mateus Sakundarno Adi (Jurnal Epidemiologi Kesehatan Komunitas, 2017)
Background : Tympanic membrane barotraumas is a rupture of tissue structure and its sequel. The initial research results show that there was 39.7% of tympanic membrane prevalence. The aim of the research was to prove the effect of several internal and external factors in traditional divers on tympanic membrane barotraumas.Method : The design used was cross sectional study strengthened by in-depth interview. The number of respondent was 130 from two groups of traditional divers taken in proportional stratiﬁed random sampling. The data analysis were univariate, bivariate, and multivariate.Results : The variables proven as the risk factors in the group of the divers who hold their breath for coins were the dive descending speed 18 meter per (p = 0.012) and without diving equipments (p = 0.018). In the group of the divers using air compressor, the signiﬁcant variables were the age of the divers in older adult 37 years old (p = 0.025).Conclusion: Several factors inﬂuencing tympanic membrane barotraumas in the group of the traditional divers who hold their breath for coins were ascending speed 18 meters per minute and without diving equipments with the probability of 39%. In the group with air compressor, the variable was the age of older adult divers ≥ 37 years with the probability of 98%.